The Effectiveness of Vocational Training Programs on Employment Outcomes - Mustajab, Duta; Irawan, Andri (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study investigates the effectiveness of vocational training programs in enhancing employment outcomes. Research Design and Methodology: Employing a quantitative descriptive approach, the study synthesizes insights from prior research to delineate the impact of vocational training on participants' employment prospects. Findings and Discussion: The literature review reveals a positive association between vocational training participation and favorable employment outcomes. High-quality programs aligned with industry needs yield more favorable outcomes. Socio-demographic factors such as age, gender, and educational attainment also influence employment prospects post-training. Additionally, vocational training contributes to socio-economic mobility and regional development. Implications: Evidence-based policy interventions and collaborations between stakeholders are essential for enhancing the effectiveness and inclusivity of vocational training programs. Addressing socio-economic disparities and ensuring program relevance is imperative for maximizing societal benefits. Longitudinal studies and comparative analyses are recommended for future research to understand further vocational training programs' long-term impacts and relative effectiveness.